Evidencing Superior Efficacy Suture Technique Outperforms Electrocoagulation in Reducing Recurrence in Ingrown Toenail Surgery - Kazez, Muhammed; Yalin, Mustafa; Ayas, Orhan; Esmez, Omer; Key, Sefa (Amer Podiatric Med Assoc, 2025)
Background: This study aimed to compare the rates of recurrence, complications, and patient satisfaction among individuals undergoing different variations of the Winograd method (WM) for the treatment of ingrown toenail, including the addition of electrocoagulation (EC) and a novel suture technique. Methods: A retrospective analysis was conducted of 605 patients who underwent surgery for ingrown toenail using the WM at two institutions. Patients were divided into four groups based on the surgical technique used: group 1 (WM + EC + new suture), group 2 (WM + EC + traditional suture), group 3 (WM + non-EC + traditional suture), and group 4 (WM + non-EC + new suture). Recurrence rates, complications, and patient satisfaction levels were assessed. Results: Group 1 demonstrated the lowest recurrence rates, whereas group 3 had the highest. Group 1 exhibited the highest satisfaction rate, whereas group 3 had the lowest. Notably, the suture technique appeared to have a greater impact on reducing recurrence rates than EC. Conclusions: Incorporating germinal matrixectomy with EC and a new suture method with the WM may improve patient satisfaction and reduce recurrence rates in ingrown toenail treatment. The suture technique appears to play a significant role in decreasing recurrence rates compared with EC. (J Am Podiatr Med Assoc 115(6), 2025; doi:10.7547/24-046)
Keywords: Winograd Method; Matrix; Matricectomy; Curettage